Field Testing a Pilot-Scale System for Alkaline Dehydration of Source-Separated Human Urine: A Case Study in Finland - Simha, Prithvi; Karlsson, Caroline; Viskari, Eeva-Liisa; Malila, Riikka; Vinnerås, Björn (Frontiers in Environmental Science, 2020)
Alkaline dehydration can treat human urine to produce a dry and nutrient-rich fertiliser. To evaluate the technology at pilot-scale, we built a prototype with capacity to treat 30 L urine d-1 and field tested it for the first time at a military training camp in Finland. We operated the system for three months and monitored the recovery of nutrients, end-product composition, physicochemical properties and energy consumption. Results revealed that the system received less urine than anticipated, but achieved high dehydration rates (30-40 L d-1m-2), recovered 30 ± 6 % N, and yielded end-products with 1.4% N, 0.9% P, and 8.3% K. However, we demonstrated that the system had potential to recover nearly 70% N and produce fertilisers containing 13.2% N, 2.3% P, and 6.0% K, if it was operated at the design capacity. The energy demand for dehydrating urine was not optimised, but we suggested several ways of reducing it. We also discussed concerns surrounding non-essential heavy metals, salts, and micropollutants, and how they can be overcome to safely recycle urine. Lastly, we pointed out the research gaps that need to be addressed before the technology can be implemented at larger scale.